Analisis Faktor – Faktor Yang Mempengaruhi Pendapatan Usahatani Jagung (Zea Mays L) Di Kecamatan Babussalam Kabupaten Aceh Tenggara - Bs, Risma Anggraini; Hanisah; Saragih, Faoeza Hafiz (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2025)
This study aims to analyze the factors influencing the income of corn farming (Zea mays L) in Babussalam Subdistrict, Southeast Aceh Regency. Data were collected through direct observation, structured interviews, and questionnaires distributed to 32 corn farmers selected using simple random sampling. The independent variables analyzed included land area (X₁), seed cost (X₂), fertilizer cost (X₃), pesticide cost (X₄), labor cost (X₅), and farming experience (X₆), while the dependent variable was farming income (Y). Data were analyzed using multiple linear regression with SPSS version 23. he results showed that all independent variables simultaneously had a significant effect on corn farming income (significance value 0.000 < α 0.05). Partially, land area, seed cost, and fertilizer cost had a significant positive effect, whereas pesticide cost, labor cost, and farming experience had no significant effect. The coefficient of determination (Adjusted R²) was 0.586, indicating that 58.6% of the variation in income was explained by the model, while the remaining 41.4% was influenced by other factors outside the model. The average income per farming unit per growing season was Rp9,397,859, or Rp13,365,845 per hectare